High-throughput calculations of spin Hall conductivity in non-magnetic 2D materials - Jiaqi Zhou; Samuel Poncé; Jean-Christophe Charlier (npj 2D Materials and Applications)
Abstract Spin Hall effect (SHE) in two-dimensional (2D) materials is promising to effectively manipulate spin angular momentum and identify topological properties. In this work, we implemented an automated Wannierization with spin-orbit coupling on 426 non-magnetic monolayers including 210 metal and 216 insulators. Intrinsic spin Hall conductivity (SHC) has been calculated to find candidates exhibiting novel properties. We discover that Y2C2I2 has an unconventional SHE with canted spin due to low crystal symmetry, Ta4Se2 is a metallic monolayer with exceptionally high SHC, and the semi-metal Y2Br2 possesses efficient charge-to-spin conversion induced by anti-crossing in bands. Moreover, quantum spin Hall insulators are investigated for quantized SHC. The present work provides a high-quality Wannier Hamiltonian database of 2D materials, and paves the way for the integration of 2D materials into high-performance and low-power-consumption spintronic devices.